PARAMETER FOR ORGANIZING HALAL TOURISM VILLAGES IN INDONESIA TO SUPPORT ECONOMIC ACTIVITIES - Handono, Wahyu Agung; Sawarjuwono, Tjiptohadi; Rohmawati, Elly Dwi (Universitas Nahdlatul Ulama Surabaya, 2024)
This study aims to identify guidelines for the implementation of halal tourism in Indonesia in order to formulate the component parameters in the implementation of Halal Tourism Village. This study used literature review as method in analyzing the data, which were 21 books indexed by web of science (SCI). The result of this study indicate that efforts to implement halal tourism villages must be able to meet the needs of tourists, namely the need for fun and the need for worship in the form of providing adequate infrastructure. As for the fulfillment of infrastructure in the halal tourism village in the form of tourist destinations, religious facilities, halal-certified food and beverage services, sharia lodging, good road access, sharia travel, and centers of typical souvenirs.